KETEGARAN UPAH NOMINAL UNTUK TURUN: KASUS UPAH NOMINAL PEKERJA PRODUKSI DI BAWAH MANDOR PADA INDUSTRI BESAR DAN SEDANG MAKANAN JADI, BAHAN PAKAIAN, KARET, DAN PLASTIK - Susanto, Joko (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2009)
This aim of the research is to test whether the decreasing productivity of the workers results in decreasing of the nominal wage of the production worker under the supervisor. Statistical data of BPS was used in this research. The research data is consist of the nominal base and over time wage of the production worker under the supervisor, productivity of workers, and capital intensity. Furthermore, this research used regression analysis with OLS estimation method. This regression analysis was based on the dynamic panel data model. Finally, this study used redundant coefficient test to reduce several insignificant regression parameters in order to get a parsimony model. The results of the research as follow: (1). the decreasing productivity of the workers does not result in decreasing the nominal base wages of the production workers under the supervisor. (2). the decreasing productivity of the workers results in decreasing of the over time wages of the production workers under the supervisor.